Impactos do metabolismo do triptofano na mucosite intestinal induzida por quimioterapia - Rafaela Ribeiro Álvares Batista (2023)
Intestinal mucositis is a frequent adverse effect in patients undergoing chemotherapy, such as with 5-Fluorouracil (5-FU), which may result in discontinuation of treatment. Previous studies suggest the importance of tryptophan metabolites (TRP) in the attenuation of inflammatory bowel diseases (IBD), via activation of the aromatic hydrocarbon receptor (AHR). Our aim was to evaluate the role of TRP metabolites and AHR activation in the response to intestinal mucositis. After treatment with 5-FU, there was a change in the concentration of kynurenine (KYN), synthesized from TRP by the enzyme indoleamine 2,3-dioxygenase 1 (IDO1), and in the microbial metabolites of TRP, concomitant with the change in AHR activity. Animals deficient in AHR (Ahr-/-) showed greater susceptibility to mucositis, increased tissue damage and intestinal permeability, simultaneously with greater bacterial translocation of Gram-positive cocci, compared to wild animals (WT). Treatment with a microbial TRP metabolite, potential AHR ligand, protected against 5-FU-induced lethality, however, did not inhibit the increase in intestinal permeability or bacterial translocation. Expression of an AHR activation target gene, cytochrome P450 enzyme family 1, subfamily A, polypeptide 1 (Cyp1a1), is reduced in the gut of IDO1-deficient animals (Ido1-/-). Ido1-/- animals also showed greater susceptibility to mucositis, accompanied by an expressive intestinal permeability, lower expression of barrier genes in relation to WT animals, alteration of the microbial metabolism of TRP and microbiota composition in relation to WT animals submitted to mucositis, including genera of bacteria that contribute to intestinal barrier function. After suggesting a protective role for TRP and AHR metabolites in mucositis, the role of Cytokine Signaling Suppressors 2 (SOCS2), which is a protein induced by AHR and associated with the control of inflammatory diseases, was evaluated. There was a reduction in the expression of Socs2 in the intestine of WT animals, simultaneously with the impairment of the integrity of the intestinal epithelium and the barrier function, in addition to a lower expression of this gene in the Ido1-/- animals. Animals deficient in SOCS2 (Socs2-/-) showed greater susceptibility to mucositis, which was associated with greater tissue damage and intestinal permeability, lower expression of barrier genes and greater bacterial translocation. Together, TRP metabolism and AHR activation play an indispensable role in protecting against 5-FU-induced intestinal mucositis by controlling tissue damage, barrier function, and bacterial translocation.